Secondary antibody deficiencies in the modern era: emerging trends, diagnostic pitfalls, and advances in personalised management - Elkhalifa, Shuayb; Salvo, Fulvio; Elbashir, Haggar; Shafiq, Irfan; Isse, Saed; Abuzakouk, Mohamed; Medhat Gaber, Mohamed; Bhana, Rehan (Frontiers in Immunology, 2025)
Secondary antibody deficiencies (SADs) are a significant but frequently under-recognised group of acquired immunodeficiencies. They may arise in various clinical settings, including haematological malignancies, immunosuppressive therapies, and protein-losing conditions. SADs are associated with an increased risk of recurrent and severe infections, hospitalisation, and impaired quality of life. Despite this, diagnostic and treatment pathways remain inconsistent across healthcare settings and regions. Recent advances in the use of structured clinical data, including electronic health records and systematic laboratory assessments, show promise in facilitating earlier recognition of SADs. These approaches support more timely treatment decisions and promote consistent standards of care. Achieving improved outcomes for individuals with SADs will require broader consensus on diagnostic criteria, treatment thresholds, and access to specialist immunology services.